Correction: Rapid and sensitive leukemia-derived exosome quantification via nicking endonuclease-assisted target recycling. Issue 33 (16th August 2022) - Zhou, Mengyang; Li, Chao; Wang, Baolong; Huang, Lin
Abstract : Correction for 'Rapid and sensitive leukemia-derived exosome quantification via nicking endonuclease-assisted target recycling' by Mengyang Zhou et al., Anal. Methods, 2021, 13, 4001–4007, ; https://doi.org/10.1039/D1AY00854D .